Pengaruh Insentif Pemerintah, Price Value dan Kesadaran Lingkungan Terhadap Minat Investasi pada Kendaraan Listrik - Kiki Septia Ihwan; Nency Revalina; Gagah Rayi Farius; Azka Khaylila Kanz; Alya Carmelia Andhini (Lokawati : Jurnal Penelitian Manajemen dan Inovasi Riset, 2025)
Investment interest in electric vehicles (EVs) in Indonesia remains relatively low despite its great potential to support the transition to clean energy. This study aims to analyze the influence of government incentives, price value perception, and environmental awareness on investment interest in electric vehicles. This research uses a quantitative approach with a survey method involving 120 respondents in the Jabodetabek area. The data were analyzed using multiple linear regression with the help of SPSS. The results show that all three independent variables—government incentives, price value, and environmental awareness—have a significant effect on investment interest, both partially and simultaneously. Among these factors, environmental awareness has the most dominant influence. The instruments used were proven valid and reliable, and the regression analysis met all the classical statistical assumptions. These findings indicate that policy support, perception of long-term benefits, and environmental concern are important factors in increasing public interest in investing in clean energy-based vehicles. This study is expected to serve as a reference for the government and industry players in designing strategies to develop the electric vehicle market in Indonesia.